2011
DOI: 10.1530/erc-10-0108
|View full text |Cite
|
Sign up to set email alerts
|

The novel Raf inhibitor Raf265 decreases Bcl-2 levels and confers TRAIL-sensitivity to neuroendocrine tumour cells

Abstract: The tumour-selective death receptor ligand tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising agent for the treatment of human cancer. However, many tumours have evolved mechanisms to resist TRAIL-induced apoptosis. A number of studies have demonstrated that aberrant PI(3)K-Akt-mTOR survival signalling may confer TRAIL resistance by altering the balance between pro-and anti-apoptotic proteins. Here, we show that neuroendocrine tumour (NET) cell lines of heterogeneous origin exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Recently, it has been shown that GOT1 cells are resistant to death receptor signalling induced by TRAIL [37]. GOT1 cells express low levels of caspase-8 and high levels of the anti-apoptotic proteins CFLAR and Bcl-2 compared to NET cells of pancreatic and broncho-pulmonary origin [37]. Our data suggest that VPA exerts a TRAIL-sensitizing effect through downregulation of CFLAR .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recently, it has been shown that GOT1 cells are resistant to death receptor signalling induced by TRAIL [37]. GOT1 cells express low levels of caspase-8 and high levels of the anti-apoptotic proteins CFLAR and Bcl-2 compared to NET cells of pancreatic and broncho-pulmonary origin [37]. Our data suggest that VPA exerts a TRAIL-sensitizing effect through downregulation of CFLAR .…”
Section: Discussionmentioning
confidence: 51%
“…A detailed analysis of the transcriptional response in GOT1 cells confirmed that there was a correlation between growth inhibition and activation of death receptor signalling and mitochondria-mediated apoptosis. Recently, it has been shown that GOT1 cells are resistant to death receptor signalling induced by TRAIL [37]. GOT1 cells express low levels of caspase-8 and high levels of the anti-apoptotic proteins CFLAR and Bcl-2 compared to NET cells of pancreatic and broncho-pulmonary origin [37].…”
Section: Discussionmentioning
confidence: 99%
“…An increase of c-FLIP protein was shown to suppress TRAILinduced gallbladder cancer cell death (41) and a decrease in c-FLIP enhanced TRAIL-mediated apoptosis in breast cancer cells (7). Likewise, Bcl-2 family proteins, namely Bcl-2 and Mcl-1, exert their inhibitory functions on TRAIL-induced apoptosis (38,40). Recently, Mcl-1 has gained increasing attention as many researchers have reported that decreasing Mcl-1 could sensitize cancer cells to TRAIL-induced apoptosis (13,14).…”
mentioning
confidence: 99%
“…8 ). Many studies indicate the importance of the Ras-Raf-MEK-ERK and the PI3K-Akt-mTOR molecular signaling pathway for NET cell growth, invasion, and proliferation [16,[40][41][42][43][44][45][46] . In addition, 5-FU showed cooperative downregulating effects with LEE011 on cell cycle components such as oncogenic cyclin D1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Single-substance treatment with everolimus has been shown to lead to resistance mechanisms in many tumor entities, including pNETs [58][59][60][61] . Dual-targeted therapy approaches to overcome possible resistance mechanisms and feedback loops have shown promising results in NETs [40,62] . In PI3K inhibitor-resistant cancer cells, combined treatment with a CDK4/6 inhibitor re-sensitized cancer cells to PI3K inhibition [63] .…”
Section: Discussionmentioning
confidence: 99%